2001
DOI: 10.1002/hc.1040
|View full text |Cite
|
Sign up to set email alerts
|

Acyl carbamoyl selenides and related sulfur isologues: synthesis and x‐ray structural analyses

Abstract: Selenocarboxylic acids [RC(‫ס‬O)SeH]were found to readily react with aryl, acyl, and arenesulfonyl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Previously, we reported that arenecarbochalcogenoic acids (ArC EE ′H, E = O, S; E ′ = S, Se, Te) react with aryl isocyanates (Ar′NCO) to give the addition products ArC EE ′C(O)NHAr′ ( E = O, S; E ′ = S, Se), the tautomer ArC EE ′C(=NAr′)(OH), which can also be detected spectroscopically 3,5,7a. In fact, ferrocenecarboselenoic acid ( 2 ) was found to readily react with 4‐methylphenyl isocyanate in ether at 25 °C to give the expected (ferrocenoyl)(4‐methylphenylcarbamoyl) selenide ( 5 ) in 94 % yield as red crystals, which showed two characteristic signals at δ = 198.9 and δ = 157.1 in the 13 C NMR spectrum, which can be ascribed to the carbonyl and carbamoyl carbon chemical shifts, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that arenecarbochalcogenoic acids (ArC EE ′H, E = O, S; E ′ = S, Se, Te) react with aryl isocyanates (Ar′NCO) to give the addition products ArC EE ′C(O)NHAr′ ( E = O, S; E ′ = S, Se), the tautomer ArC EE ′C(=NAr′)(OH), which can also be detected spectroscopically 3,5,7a. In fact, ferrocenecarboselenoic acid ( 2 ) was found to readily react with 4‐methylphenyl isocyanate in ether at 25 °C to give the expected (ferrocenoyl)(4‐methylphenylcarbamoyl) selenide ( 5 ) in 94 % yield as red crystals, which showed two characteristic signals at δ = 198.9 and δ = 157.1 in the 13 C NMR spectrum, which can be ascribed to the carbonyl and carbamoyl carbon chemical shifts, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, in spite of their wide application, only a few methodologies have been reported for the preparation of selenocarbamates. These approaches generally rely on the reactivity of isocyanates with selenium‐centered nucleophiles such as selenocarboxylic acids [12] or selenolates, generated by means of reductive cleavage of diselenides with Zn/AlCl 3 [13] . N ‐Alkyl‐ Se ‐alkylselenocarbamates can be prepared from isocyanates and haloalkanes by using LiAlHSeH as the selenating reagent [14] .…”
Section: Introductionmentioning
confidence: 99%